Imprisoned bodies - free minds: Incarcerated women and liberatory learning. - Irene C. Baird (Adult Education Research Conference, 1997)
Using women's literature as a medium for self-exploration for self-awareness, incarcerated women learn to free their minds from their limiting situation. Examining the model through prison, Freirian, feminist methodologies affirms its significance/effectiveness as the essential first step for saying things differently, for liberation from oppression.